Pengaruh Fasilitas dan Promosi Terhadap Minat Kunjungan Wisatawan di Maribaya Natural Hot Spring Resort - Anti Riyanti; Zaidan Hibatulloh (Manajemen dan Pariwisata, 2026)
Tourism is one of the economic drivers that has a broad impact on people's welfare. This study examines how facilities and promotions affect tourists' interest in visiting Maribaya Natural Hot Springs. This study uses facilities and promotions as independent variables and interest in visiting as the dependent variable. The researcher used a quantitative research method with determined respondents and the use of multiple simple regression to determine how much influence each independent variable has on the dependent variable, either individually or simultaneously. The results of the study indicate a strong relationship between the variables of facilities and promotions on the variable of interest in visiting. Regarding the results of the study, the author suggests maintaining and improving facilities, reviewing the use of promotions that do not have much impact, and starting to be more active in using advertising on social media platforms.